Discover answers to your questions with Westonci.ca, the leading Q&A platform that connects you with knowledgeable experts. Connect with a community of experts ready to provide precise solutions to your questions on our user-friendly Q&A platform. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
To solve the given problem, let's define the variables first. Let [tex]\( J \)[/tex] be the cost of the jacket and [tex]\( s \)[/tex] be the cost of the slacks. According to the problem, we have two pieces of information:
1. The total cost of the jacket and the slacks is \[tex]$63. 2. The jacket costs \$[/tex]33 more than the slacks.
These pieces of information can be translated into the following system of equations:
[tex]\[ J + s = 63 \][/tex]
[tex]\[ J - s = 33 \][/tex]
To solve this system of equations, we can use the method of addition (also known as the elimination method). By adding both equations together, we can eliminate one of the variables. Here’s how it works:
[tex]\[ J + s = 63 \][/tex]
[tex]\[ J - s = 33 \][/tex]
Adding these equations together:
[tex]\[ (J + s) + (J - s) = 63 + 33 \][/tex]
[tex]\[ 2J = 96 \][/tex]
Now, divide both sides by 2 to solve for [tex]\( J \)[/tex]:
[tex]\[ J = \frac{96}{2} \][/tex]
[tex]\[ J = 48 \][/tex]
So, the jacket costs \[tex]$48. Now, to determine the cost of the slacks \( s \), we can substitute \( J = 48 \) back into one of the original equations. Let's use the first equation: \[ 48 + s = 63 \] Subtract 48 from both sides to solve for \( s \): \[ s = 63 - 48 \] \[ s = 15 \] So, the slacks cost \$[/tex]15.
Therefore, Mr. Rose paid \[tex]$48 for the jacket and \$[/tex]15 for the slacks.
The correct system of equations that represents the word problem is:
[tex]\[ J + s = 63 \][/tex]
[tex]\[ J - s = 33 \][/tex]
1. The total cost of the jacket and the slacks is \[tex]$63. 2. The jacket costs \$[/tex]33 more than the slacks.
These pieces of information can be translated into the following system of equations:
[tex]\[ J + s = 63 \][/tex]
[tex]\[ J - s = 33 \][/tex]
To solve this system of equations, we can use the method of addition (also known as the elimination method). By adding both equations together, we can eliminate one of the variables. Here’s how it works:
[tex]\[ J + s = 63 \][/tex]
[tex]\[ J - s = 33 \][/tex]
Adding these equations together:
[tex]\[ (J + s) + (J - s) = 63 + 33 \][/tex]
[tex]\[ 2J = 96 \][/tex]
Now, divide both sides by 2 to solve for [tex]\( J \)[/tex]:
[tex]\[ J = \frac{96}{2} \][/tex]
[tex]\[ J = 48 \][/tex]
So, the jacket costs \[tex]$48. Now, to determine the cost of the slacks \( s \), we can substitute \( J = 48 \) back into one of the original equations. Let's use the first equation: \[ 48 + s = 63 \] Subtract 48 from both sides to solve for \( s \): \[ s = 63 - 48 \] \[ s = 15 \] So, the slacks cost \$[/tex]15.
Therefore, Mr. Rose paid \[tex]$48 for the jacket and \$[/tex]15 for the slacks.
The correct system of equations that represents the word problem is:
[tex]\[ J + s = 63 \][/tex]
[tex]\[ J - s = 33 \][/tex]
We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.